A medical student‘s guide to the slit lamp examination - Ruparelia, Sunil (DALHOUSIE MEDICAL JOURNAL, 2023)
The slit lamp is an essential tool for the diagnosis of common eye pathology. Despite many eye conditions presenting initially to primary care, medical students do not typically receive formal training with the slit lamp in standard medical education curriculum. This guide provides a consistent, systematic framework that may be used by students and clinicians when approaching a slit lamp examination. Additionally, suggestions intended to optimize examination outcomes are described. It is our hope that this guide serves to enhance medical student comfort and proficiency with eye examinations, be it in an ophthalmology clinic, primary care, or emergency department setting.